2018
DOI: 10.19206/ce-2018-401
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the test drive cycle conditions impact on exhaust emissions from an internal combustion engine

Abstract: Test results of exhaust emission sensitivity to engine operating conditions from a vehicle with a compression ignition engine have been analyzed. These results were determined in driving tests: NEDC (New European Driving Cycle), RDE (Real Driving Emissions) and Malta, an original drive cycle developed at Poznan University of Technology. The tests in the NEDC and Malta cycles were carried out on the engine dynamometer in driving tests simulation conditions, while the RDE test was carried out in the real conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…The test was carried out under urban conditions in the city of Poznan, rural conditions around the city of Poznan including an expressway portion (S11) and motorway conditions-the S11 expressway and the A2 motorway [14,26,27] (Figure 3). The total distance of the test route was approx.…”
Section: Aim Object Program Of Investigations and Research Equipmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The test was carried out under urban conditions in the city of Poznan, rural conditions around the city of Poznan including an expressway portion (S11) and motorway conditions-the S11 expressway and the A2 motorway [14,26,27] (Figure 3). The total distance of the test route was approx.…”
Section: Aim Object Program Of Investigations and Research Equipmentmentioning
confidence: 99%
“…Majority of publications pertains to engine testing in research tests based on the averaged values [14][15][16][17][18][19][20]. Such engine are homologation test ones performed on a chassis dynamometer whose characteristic feature is that the processes of velocity and motion resistance may be deemed as determined based on the repeatability of the tests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of data allows to perform numerous studies on the distribution of engine performance under normal operating conditions. The authors of paper [1] show that the conditions of real operation significantly differ from the conditions of tests conducted as part of vehicle type approval. They showed that the differences between emissions in the test and in reality are significantly greater.…”
Section: Introductionmentioning
confidence: 97%
“…Second, reducing emissions by non-engine methods (aftertreatment), i.e. the use of a combination of catalytic reactors and particulate filters, such as TWC -Three Way Catalyst [6,20].…”
Section: Introductionmentioning
confidence: 99%